APPLICATION OF INFORMATION TECHNOLOGIES FOR MANAGEMENT DECISION MAKING IN THE CONDITIONS OF THE INSTABILITY OF THE EXTERNAL ECONOMIC SPACE - Dmytro Kabachenko; Olena Churikanova; Svitlana Oneshko; Ruslan Avhustyn; Valeria Slatvinska (International Journal for Quality Research, 2022)
The objective of the article lies in determining the place of information technologies in the process of making management decisions, as well as determining the current level of their implementation with the formation of forecasts for the near-term prospect. Methodology. The assessment of the level of information technology development has been carried out on the basis of Statista (2021) and Gagliodi (2020) data by applying deduction methods, graphical and comparative methods. Results. The analysis of statistical data has revealed that the growth rate of the use of information technology in management decision making has slowed down in 2020-2021. The data obtained show that the IT market is currently focused on the supply of devices and software for remote working. Services on supporting decision-making are used less often, although in the current unstable environment, they should be the ones to pull the focus of leaders onto themselves.